Tingkat Kemampuan Literasi Informasi Mahasiswa Berdasarkan Standard Association of College and Research Libraries - Mulida Djamarin; Thamrin Hasan (Jurnal Gema Pustakawan, 2023)
Selectively selecting information that suits your needs requires skills in information literacy. This study aims to determine the level of students' information literacy skills based on the Association of College and Research Libraries (ACRL) Standards in the nursing faculty library at Riau University. This research is quantitative descriptive. The research population was all students from the nursing faculty at Riau University, a total of 822 respondents. The population was sampled as 270 respondents based on Slovin's formulation. Sampling was carried out using accidental sampling technique. The data collection method uses a questionnaire. The questionnaire used in this study is a closed questionnaire with a four-category Likert scale, created based on ACRL standards. Then, the data processing technique is by data checking, coding, and tabulation. Meanwhile, the data analysis technique uses descriptive analysis. The results of the study show that the information literacy skills of FKp Riau University students are very good. Students are able to carry out 22 activity indicators contained in the 5 components of the Association of College and Research Libraries (ACRL) information literacy competency standards. 91.63% of respondents answered always and often on the first standard component, 88.76% on the second standard component, 92.80% on the third standard component, 93.45% on the fourth standard component, and 91.73% on the fifth standard component . From the results of this study, it can be concluded that the students' information literacy level has demonstrated a very good level of information literacy skills.